Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.3390/ijms20246238
|View full text |Cite
|
Sign up to set email alerts
|

Primary Neurons and Differentiated NSC-34 Cells Are More Susceptible to Arginine-Rich ALS Dipeptide Repeat Protein-Associated Toxicity than Non-Differentiated NSC-34 and CHO Cells

Abstract: A repeat expansion mutation in the C9orf72 gene is the most common known genetic cause of amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD). In this study, using multiple cell-based assay systems, we reveal both increased dipeptide repeat protein (DRP) toxicity in primary neurons and in differentiated neuronal cell lines. Using flow cytometry and confocal laser scanning microscopy of cells treated with fluorescein isothiocyanate (FITC)-labeled DRPs, we confirm that poly-glycine-arginine (GR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 42 publications
2
8
0
Order By: Relevance
“…Toxicity of polyGR/PR has been observed in cell culture systems (Mori et al, 2013 ; Kwon et al, 2014 ; Kramer et al, 2018 ), in Drosophila models (Mizielinska et al, 2014 ; Wen et al, 2014 ), and in mouse models (Zhang et al, 2018 ; 2019 ; Choi et al, 2019 ; Cook et al, 2020 ). We also demonstrated consistent and significant cell type and differentiation-specific toxicity of polyGR/PR in cell culture models (Gill et al, 2019 ).…”
Section: Introductionsupporting
confidence: 79%
“…Toxicity of polyGR/PR has been observed in cell culture systems (Mori et al, 2013 ; Kwon et al, 2014 ; Kramer et al, 2018 ), in Drosophila models (Mizielinska et al, 2014 ; Wen et al, 2014 ), and in mouse models (Zhang et al, 2018 ; 2019 ; Choi et al, 2019 ; Cook et al, 2020 ). We also demonstrated consistent and significant cell type and differentiation-specific toxicity of polyGR/PR in cell culture models (Gill et al, 2019 ).…”
Section: Introductionsupporting
confidence: 79%
“…Our lab has reported that exogenous application of GR 15 and PR 15 to NSC-34 cells induces cellular toxicity, as measured by WST-1 metabolism, LDH release, BrdU labeling, and Caspase-3 activity (Gill et al, 2019). In the present study, we use the WST-1 metabolism and LDH release assays to evaluate changes in DRP toxicity in the presence of a PRMT inhibitor.…”
Section: Resultsmentioning
confidence: 98%
“…For example, when administered exogenously to U2OS cells, synthetic GR 20 and PR 20 are shown to bind to nucleoli, disrupt RNA splicing and processing, and decrease cell viability (Mori et al, 2013). Our lab has previously demonstrated that exogenous application of synthetic GR 15 and PR 15 to mouse spinal cord neuroblastoma hybrid cells (NSC-34) induces cellular toxicity, as measured by various cell health and function assays and that this toxic effect becomes more severe as the cells are further differentiated toward neurons, with primary neurons exhibiting the greatest toxicity (Gill et al, 2019). In addition, a series of studies involving the expression of the repeat expansion in Drosophila have demonstrated polyGR and polyPR related toxicity (Mizielinska et al, 2014;Freibaum et al, 2015;Lee et al, 2016), with one study revealing the disruption of stress granule assembly due to the presence of polyGR and polyPR (Lee et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Quantitative resistances are effective at later growth stages and are therefore referred to as field resistance or adult plant resistance (APR, Krattinger and Keller 2016 ). To date, more than 80 resistance genes to leaf rust ( Lr genes) have been identified in bread wheat, durum wheat, and diploid wheat species (Gill et al 2019 ). While most of them show race-specific resistance at the seedling stage, genes like Lr12 , Lr13 , Lr22a/b , Lr34 , Lr35 , Lr37 , Lr46 , Lr67 , Lr68 , and Lr77 confer resistance at the adult plant stage (Dakouri et al 2013 ; McIntosh et al 2013 , 2017 ).…”
Section: Introductionmentioning
confidence: 99%